2003
DOI: 10.1021/ef020165o
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Method for the Prediction of Coal Ash Slag Viscosity

Abstract: A new method for the prediction of the viscosity of coal ash slags, in the Newtonian region, is presented. The technique is modeled on experimental viscosity data less than 1000 Pa s and hence is most reliable in that region. The capability of the model in predicting the viscosity of slags from coal ash was found to be superior to a number of the most commonly used empirical models found in the literature, which are based on simplified oxide melts or British coal ash slags. The method also provides an indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 9 publications
1
91
0
Order By: Relevance
“…Because of the difficulty in measuring the viscosity at high temperatures, several correlations based on the slag composition have been proposed [23,[27][28][29][30]. However, these correlations exhibited deviations from the measured data depending on the ash samples [31][32][33] and with each other [34].…”
Section: Effects Of Slag Properties: Viscositymentioning
confidence: 99%
“…Because of the difficulty in measuring the viscosity at high temperatures, several correlations based on the slag composition have been proposed [23,[27][28][29][30]. However, these correlations exhibited deviations from the measured data depending on the ash samples [31][32][33] and with each other [34].…”
Section: Effects Of Slag Properties: Viscositymentioning
confidence: 99%
“…To be useful for deposition modelling, ash viscosity must be described as a function of particle temperature and ash composition. In the current paper a model proposed in (Browning et al, 2003) is used. The model is a function of mole fractions of Si, Al, Ca, Fe, Mg, Na, K, Mn, Ti, S and provides improvements over other models in matching experimental data.…”
Section: Deposit Formation Modelmentioning
confidence: 99%
“…Browning et al [15] provide a brief review of the various slag viscosity models, and they observed that the Kamanovitch-Urbain method is the most accurate for SiO 2 -Al 2 O 3 -CaO-MgO slags. They also suggested an empirical method to obtain the viscosity of the slag that depends on finding the temperature shift, among other parameters.…”
Section: A Brief Review Of Various Viscosity Modelsmentioning
confidence: 99%
“…Such a sharp gradient causes various types of responses including the creation of different sub-layers. Studies have indicated that slag viscosity must be within a certain range of temperatures for tapping and for the membrane wall to be accessible, for example, between 1,300 °C and 1,500 °C, the viscosity is approximately 25 Pa·s [15].…”
Section: Introductionmentioning
confidence: 99%